Prevalence of Methicillin-Resistant Staphylococcus aureus in Hospitals of Kathmandu Valley - Mukhiya, Reena K; Shrestha, Anima; Rai, Shiba K; Panta, Kritu; Singh, RN; Rai, Ganesh; Prajapati, Amita (Nepal Journal of Science and Technology, 2013)
NOTE: The first author (Reena K. Mukhiya) was omitted as an author of this paper in the table of contents for this issue and on the webpage. This was an error. Reena Mukhiya was always included as the first author on the PDF of the article. 11 December 2014. Present study was conducted to determine the prevalence of nosocomial pathogen methicillin resistant Staphylococcus aureus in hospital environment samples (surface swabs and air, n=188) and health care workers (nose and hand, n=162) of hospitals located in Kathmandu valley. The samples were studied following the standard protocols. Of the 61 S. aureus, 20.9% and 14.3% were isolated from health personnel and hospital environment respectively. Of 20.9% S. aureus in hospital environment, 6.6% were isolated from OPD and 17.9% from wards. Similarly, in HCWs 28.3% and 13.5% were hand and nasal carrier respectively. In total, 45.9% were MRSA. Among MRSA isolates, 50% were from HCWs whereas, 40.7% from hospital environment. The most effective antibiotic for all isolates was vancomycin with 100% efficacy. The isolates had relatively high rate of resistance to cefixime (44.0%), followed by co-trimoxazole (28.0%), erythromycin (23.0%), gentamicin (18.0%), tetracycline (16.0%) and ofloxacin (8.0%). Since MRSA prevalence was not reduced, so indicates regular surveillance of nosocomial infection, hand hygiene improvement strategies and monitoring of antimicrobial susceptibility pattern. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 185-190 DOI: http://dx.doi.org/10.3126/njst.v13i2.7734